(untitled) (Boletín de Investigaciones Marinas y Costeras, 2016)
Two species of the crab family Cryptochyridae, Opecarcinus hypostegus (Shaw and Hopkins) and Troglocarcinus corallicola Verrill, are reported for the first time on the Caribbean coast of Colombia, thus extending the known distribution of the two species. For both species a short diagnosis and remarks on their distribution, depth range and association with corals are included.